A new species of Chilenoperla (Plecoptera: Gripopterygidae) from the Andes of South America - Vera, Alejandro (Zootaxa, 2012)
Chilenoperla puelche n. sp. is described based on male and female adults and one nymph. The wing color pattern and the gen-italia of the adults are diagnostic clearly distinguishing it from the other species of the genus. However, the nymph is similar tothat of C. elongata Vera. This new species is distributed in the Andes Mountains of Chile from 38° to 39° south latitude; Adults were collected in September and November.